Preparation and thermoelectric properties of sulfur doped Ag2Te nanoparticles via solvothermal methods - Zhou, Wenwen (2013)
In this work, n-type Ag2Te nanoparticles are prepared by a solvothermal approach with uniform and controllable sizes, e.g. 5–15 nm. The usage of dodecanethiol during the synthesis effectively introduces sulfur doping into the sample, which optimizes the charge carrier concentration of the nanoparticles to >1 × 1020 cm−3. This allows us to achieve the desired electrical resistivities of <5 × 10−6 Ω m. It is demonstrated that Ag2Te particles prepared by this solvothermal process can exhibit high ZT values, e.g. 15 nm Ag2Te nanoparticles with effective sulphur doping show a maximum ZT value of ~0.62 at 550 K.